Guideline of an Economics instruction for enhancing economic literacy of lower secondary students - Yaungyuen, Ronnajuk; Sawekngam, Wichai (An Online Journal of Education, 2025)
This research aimed to 1) study economic literacy for lower secondary school students and 2) propose an economics teaching approach to promote economic literacy for lower secondary school students. The study was divided into 2 phases: Phase 1: The study of economic literacy. The target group was 5 economics experts. The research instrument was in-depth interviews. Phase 2: The study of economics teaching approaches to promote economic literacy. The target group was 5 curriculum and instruction experts. The sample was 144 lower secondary school students. The research instruments included interviews, group discussions, and the developed teaching approach. Data was analyzed by content analysis. The research results found that 1) economic literacy refers to the ability to apply knowledge, skills, and attitudes to analyze the mechanisms of the economic system. It is divided into 4 aspects: (1) economic system, (2) production, (3) consumption, and (4) finance and investment, and 2) teaching approaches. It uses a four-point conceptual framework, the PACE approach, consisting of (1) P (Practice, practice from real situations), (2) A (Analyze, analyze problems logically), (3) C (Create, create alternatives appropriate to the context), and (4) E (Empower, promote the use of knowledge for real life and the community), with two teaching and learning approaches: (1) promotion through integration of social studies subjects, and (2) promotion through activities.